Cone-spiral magnetic ordering dominated lattice distortion and giant negative thermal expansion in Fe-doped MnNiGe compounds. Issue 3 (12th December 2019) - Shen, Feiran; Zhou, Houbo; Hu, Fengxia; Wang, Jian-Tao; Deng, Sihao; Wang, Baotian; Wu, Hui; Huang, Qingzhen; Wang, Jing; Chen, Jie; He, Lunhua; Hao, Jiazheng; et al.
Abstract : By utilizing the large lattice distortion caused by incommensurate cone-spiral magnetic ordering and the induced texture effect in Fe-doped MnNiGe alloys, NTE largely exceeding the average crystallographical contribution has been achieved. Abstract : Negative thermal expansion (NTE) has emerged as one of the intense research topics to meet the demands of the precision industry for compensating positive thermal expansion (PTE) properties. The adjustment of the NTE behavior is the key for tailoring thermal expansion. Chemical modification and the particle size effect have been regarded as effective means to tune the NTE behavior, and the crystallographic contribution is usually the upper limit of NTE. Here, we reported a new way to tune the NTE behavior involving lattice distortion that is dominated by the magnetic structure in hexagonal MnM′Ge-based (M′:Ni, Co) alloys. The achieved maximal linear NTE reached Δ L / L ∼ −23 690 × 10 −6 (  = −121.5 × 10 −6 K −1 ) in a temperature interval as wide as ∼195 K (80–275 K) for Fe-doped MnNiGe alloys. This value was 3.3 times larger than that of the corresponding average crystallographical contribution and exceeded that of almost all NTE materials reported to date. Neutron powder diffraction and first-principles calculations were carried out. The results revealed that Fe-doped MnNiGe showed incommensurate cone-spiral magnetic ordering, and the lattice distortion during the phase transition was more significant than that of MnCoGeIn with linear ferromagnetic ordering. The larger lattice distortion favored the cleavage of the hexagonal phase along the c -axis. As a result, a texture effect along the (110) crystal plane occurred during the molding process, which greatly enhanced the amplitude of the isotropic in-plane linear NTE. The present study provides a new strategy for exploring adjustable NTE behaviors.